V. Stratigraphic Observation of the Surface Snow Cover in West Enderby Land, East Antarctica, 1970-1971 - ワタナベ, オキツグ; WATANABE, Okitsugu (National Institute of Polar Research, 1972)
P(論文) departmental bulletin paper